Gestational high-sucrose diet mediated vascular hyper-contractility in mesenteric arteries from offspring - Xinying Liu; Meng Liu; Chunxia Wang; Liting Duan; Qinggui Ren; Shuli Jiang; Jing Han; Hongwei Fu; Xiao Sun; Dongmei Man; Xueqin Feng (Scientific Reports)
Abstract Prenatal high sucrose diet (HS) generates profound effects on vascular diseases in offspring later in life. This study aimed to determine whether and how prenatal HS affect vasoreactivity in resistance arteries from adult offspring. Pregnant Sprague-Dawley rats were fed with normal drinking water or 20% high-sucrose solution during the whole gestational period. Mesenteric arteries (MAs) from adult offspring were obtained and tested for vascular functions with DMT. The whole-transcriptome sequencing (RNA-seq) of MAs was performed to reveal the different genes and possible pathway. Real-time PCR and western blot were performed to access mRNA and protein expression. The thicker smooth muscle layer and mitochondrial swelling were observed in MAs in HS offspring. Prenatal HS mediated higher vasoconstriction/vascular sensitivity induced by phenylephrine (PE) and 5-Hydroxytryptamine (5-HT). RNA-Seq analysis revealed that the genes crystallin alpha B (CYRAB) and heat shock protein family E member 1 (HSPE1) were upregulated, while the gene adenomatous polyposis coli downregulated 1 (APCDD1) was downregulated in HS group, confirmed at mRNA and protein expression levels. Wingless-related integration site (Wnt)/Ca2+ indicated by KEGG analysis was the essential pathway inducing vascular dysfunction in HS group. As a Wnt5a inhibitor, Box5 reduced MA tension induced by PE or 5-HT in HS group. Both protein kinase C (PKC) inhibitor-GF109203X and Inositol 1,4,5-trisphosphate receptor (IP3R) inhibitor-2-Aminoethoxydiphenyl borate (2-APB) significantly decreased MA tone in HS group. Ca2+ levels in MAs were markedly higher in HS offspring than in control (CON), likely contributing to enhanced vascular reactivity. Vascular relaxation induced by acetylcholine (ACh) in HS was lower than that in CON. N(G)-Nitro-l-arginine methyl ester (L-NAME) increased PE-mediated vascular tension in CON group, while no effect in HS group, suggesting that endothelial nitric oxide (NO) system dysfunction in MAs exposed to prenatal HS. This study demonstrated that prenatal HS induced hyper-vasocontraction in MAs from adult offspring, which was associated with the enhanced Wnt5a-PKC/IP3R-Ca2+ pathway and decreased endothelial NO function.